Index/Ring Finger Ratio, Hand and Foot Index: Gender Estimation Tools - Gupta, Sonia (J Clin Diagn Res, 2017)
INTRODUCTION: Gender estimation from dismembered human body parts and skeletal remains in cases of mass disasters, explosions, and assaults cases is an imperative element of any medico-legal investigations and has been a major challenge for forensic scientists. AIM: The aim of the present study was to estimate the gender by using index and ring finger length ratio, hand and foot index along with the correlation of both the hand and foot index to determine the vital role of all the indices in establishing gender identity. MATERIALS AND METHODS: A descriptive cross-sectional study was done on 300 subjects (150 males and 150 females). Various anthropometric measurements like hand length, hand breadth and hand index, Index Finger Length (IFL), Ring Finger Length (RFL) and IFL/RFL ratio as well as foot length, foot breadth and foot index were estimated in millimeters (mm) with the help of sliding-anthropometric caliper. The data was analysed using independent t-test and Pearson correlation coefficient test. A probability value (p) of ≤ 0.05 was considered statistically significant. RESULTS: The index and ring finger ratio was found to be higher in females as compared to males. The hand and foot index was more in males than in females. The index and ring finger length ratio, hand and foot index between males and females was found to be statistically significant for both hands and feet. A statistically significant correlation was determined between hand indexes versus foot index. CONCLUSION: This study can be useful to establish the gender of a dismembered hand or foot when subjected for medicolegal examination.